Teaching Standards and Curriculum Review : Final Report - Johnson, David (Washington, DC : World Bank, 2022)
The Service Delivery Indicators (SDI) report "Teaching Standards & Curriculum Review" carries out a review of African primary curriculums to map the common learning themes and requirements for mathematics and language (based on the official language of instruction at the grade four level) across the primary curriculum.